An organic-inorganic composite admixture, a preparation method thereof, and its application in a calcined clay-limestone low-carbon cement system

By using organic and inorganic composite admixtures in the calcined clay-limestone low-carbohydrate cement system, and using β-CD and POM units to modify the molecular structure of the polycarboxylic acid admixture, the problem of poor adaptability of traditional admixtures in this system is solved, and efficient water reduction and improvement of construction performance is achieved.

CN119751761AActive Publication Date: 2025-04-04JIANGSU SOBUTE NEW MATERIALS CO LTD +1

Patent Information

Application Number
CN202510259027.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-04
Estimated Expiration
2045-03-06

AI Technical Summary

Technical Problem

Traditional comb cement dispersants have poor adaptability in calcined clay-limestone low-carbohydrate cement systems, resulting in insufficient initial water reduction rate and large slump loss.

Method used

The molecular structure of organic and inorganic composite admixture is used. The molecular structure of the polycarboxylic acid admixture changes the solution conformation of the polycarboxylic acid admixture by introducing β-CD and POM units, avoids interaction with clay particles, and uses the steric steric resistance generated by the side chain to improve the dispersion performance.

Benefits of technology

It significantly improves the resistance of admixtures to clay in LC3 system and improves the construction performance of concrete, including improving the initial flow and time flow.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_9
    Figure SMS_9
  • Figure SMS_10
    Figure SMS_10
  • Figure SMS_11
    Figure SMS_11
Patent Text Reader

Abstract

An organic-inorganic composite admixture, a preparation method thereof, and an application thereof in a calcined clay-limestone low-carbon cement system. The organic-inorganic composite admixture is prepared by free radical copolymerization of unsaturated carboxylic acid, 2-acrylamido-2-methylpropanesulfonic acid, methacryloyl trimethyl ammonium chloride or acryloyl trimethyl ammonium chloride, maleic anhydride grafted β-cyclodextrin, an oxidant and a reductant, and then an electrostatic assembly reaction with POM polyoxometalate. The present invention forms a spatial cross double network structure through the characteristics of β-cyclodextrin and polyoxometalate POM structure, resulting in a large steric hindrance, forming a sufficiently thick adsorption layer, and hindering the competitive adsorption of clay to the admixture; dual adsorption sites are formed by the carboxyl and sulfonic acid groups on the main chain and the side chain, further enhancing the admixture to LC 3 The dispersing ability of the system ultimately achieves the characteristics of low dosage, high water reduction rate and excellent collapse retention performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to an organic-inorganic composite admixture, a preparation method thereof, and application thereof in a calcined clay-limestone low-carbon cement system. Background Art

[0002] In recent years, with the rapid growth of population and the improvement of urbanization level, the demand for related urban infrastructure has continued to increase, which has also driven the growth of cement production. However, the manufacturing process of traditional cement not only consumes a large amount of natural raw materials, but also produces a large amount of CO 2 Carbon emissions have long been at the forefront of global carbon emissions. Therefore, in order to reduce the impact of cement production on natural resources and the environment, the CO 2 The development and application of high-performance auxiliary cementitious materials to replace cement and clinker in large quantities is internationally recognized as one of the most important technical approaches for low-carbon development of the cement and concrete industry.

[0003] Domestic and foreign scholars have been studying new low-carbon cementitious systems for a long time, among which limestone calcined clay cement (LCC) 3 ) originated from the research of the Swiss Federal Institute of Technology (Lausanne) and is a cement composed of limestone, calcined clay, gypsum and clinker. 3 In the process, limestone reacts with calcined clay to form carbon aluminate hydrate, which promotes cement hydration. The hydration product increases with the increase of calcined clay content. 3 At a higher cement clinker replacement rate, it still has higher mechanical properties, LC 3 -X in X represents the ratio of clinker mass to total cement mass. The most typical LC 3 The LC-50 mix contains 50% Portland cement clinker, 30% calcined clay, 15% limestone powder and 5% gypsum. Since calcined clay does not produce carbon emissions during the heating process and its calcination temperature is lower than that of cement clinker, compared with traditional cement, LC-50 has a higher carbon content than traditional cement. 3 Replacing half of the clinker can reduce carbon dioxide emissions by about 40%.

[0004] However, studies have shown that LC 3The performance of the system concrete is worse than that of ordinary silicate cement concrete, which is caused by the layered structure and surface electrical properties of clay. At present, the traditional comb-type polycarboxylic acid admixture PCE is particularly sensitive to the amount of clay and has poor adaptability, especially in terms of initial fluidity and loss of fluidity over time. This is because the PCE side chain is easily inserted into the layered structure of clay, which causes its dispersibility to drop sharply, resulting in poor water reduction performance. Secondly, although the surface of calcined clay particles is negatively charged, in cement paste, through Ca 2+ The complexation will also cause the negatively charged PCE to anchor on the clay surface and thus fail to continuously play a dispersing role. Therefore, the traditional comb-type polycarboxylic acid admixture cannot be well applied to LC 3 In concrete systems, the LC problem is solved by modifying the molecular structure of the admixture. 3 The issue of system performance has attracted widespread attention from researchers in related concrete technology.

[0005] The Chinese patent application with publication number CN 117105595 A discloses a low-carbon engineering cement-based composite material and its preparation method, which is prepared by the following components in weight proportion: 240-370 parts of cement, 550-650 parts of calcined clay, 140-330 parts of lightly burned dolomite powder, 340-370 parts of quartz sand, 26 parts of PVA fiber, 425 parts of water, and 3-4.5 parts of high-efficiency water reducer. Compared with traditional high-ductility cement-based composite materials, it has significantly improved mechanical properties, greatly reduced shrinkage, and has obvious strain hardening and multi-crack cracking characteristics. However, the patent application does not give a specific high-efficiency water reducer structure, and does not report its effect on working performance.

[0006] The Chinese patent application with publication number CN115959870 A discloses a crack-resistant low-carbon high-performance concrete and a preparation method thereof, wherein the raw materials and their amounts include: LC 3 Cementitious materials 390~410 kg / m 3 , sand 640~660 kg / m 3 , stone 1000~1100 kg / m 3 , water 150~170 kg / m 3 , water reducing agent 8.0~8.5 kg / m 3 , activated carbon fiber 0.1~0.3 kg / m 3 , graphene oxide 0.1~0.3 kg / m 3 LC 3The cementitious material is mainly composed of cement, calcined clay, limestone powder and gypsum; the water is a mixture of wastewater from a mixing station and clean water. The water reducer is a polycarboxylic acid water reducer with a solid content of 20% and a water reduction rate of 19%. The above PCE structure does not mention whether it contains an anti-clay group, resulting in the system having no obvious advantages in slump and expansion. Summary of the invention

[0007] Technical problems to be solved: In view of the poor adaptability of traditional comb-type cement dispersants and clay-containing materials in the prior art, such as insufficient initial water reduction rate and large slump loss, the present invention proposes an organic-inorganic composite admixture and a preparation method thereof and its application in a calcined clay-limestone low-carbon cement system. From the perspective of changing the molecular solution conformation of the polycarboxylic acid admixture, by introducing amphiphilic functional groups, it avoids interaction with clay particles and does not form an intercalation structure with the clay; by introducing monomers with significant steric effects, it further avoids intercalation adsorption and improves the dispersion performance by utilizing the steric hindrance generated by the side chain; the synthetic side chain does not contain -CH 2 -CH 2 -O-structured admixture to improve the mud resistance of polycarboxylic acid admixture.

[0008] Technical solution: An organic-inorganic composite admixture, whose raw materials include the following components: monomer A, monomer B, monomer C, monomer D, polyoxometalate POM, oxidant and reductant, wherein monomer A is an unsaturated carboxylic acid, monomer B is 2-acrylamido-2-methylpropanesulfonic acid (AMPS), monomer C is methacryloylpropyltrimethylammonium chloride (MAPTAC) or acrylamidopropyltrimethylammonium chloride (APTAC), monomer D is maleic anhydride grafted β-cyclodextrin (MAH-β-CD), the mass ratio of monomer A, monomer B, monomer C and monomer D is 70: (15~25): 10: (0.5~1.5), the mass ratio of the added amount of polyoxometalate to the monomer C is 1:1.1~1.4, the amount of the oxidant is 0.1~0.5 wt% of the total mass of the monomers, and the mass ratio of the reductant to the oxidant is 1:2.

[0009] Preferably, the polyoxometalate POM is phosphomolybdic acid H 3 [PMo 12 O 40 ] or silicomolybdic acid H 4 [SiMo 12 O 40 ], both polyoxometalates are commercially available, among which [SiMo 12 O 40 ] 4- and [PMo 12 O 40 ] 3-The anionic groups are able to undergo charge assembly with the cationic tertiary amine groups of MAPTAC or APTAC.

[0010] Preferably, the oxidant is a water-soluble azo oxidant, ammonium persulfate, sodium persulfate or potassium persulfate.

[0011] Preferably, the reducing agent is at least one of sodium pyrosulfite, sodium sulfite, sodium bisulfite, sodium dithionite, sodium thiosulfate and ferrous sulfate.

[0012] Preferably, the structural formula of the unsaturated carboxylic acid monomer A is shown in the following formula (I):

[0013] (I)

[0014] In the formula, R 1 H or CH 3 , R 2 It is H or alkali metal ion.

[0015] Furthermore, the structural formula of monomer B is shown in the following formula (II):

[0016] (II).

[0017] Furthermore, the structural formula of monomer C is shown in the following formula (III):

[0018] (III),

[0019] In formula (III), R 3 H or CH 3 .

[0020] Furthermore, the structural formula of monomer D is shown in the following formula (IV):

[0021] (IV),

[0022] In formula (IV), M represents an alkali metal ion.

[0023] Based on the above-mentioned method for preparing an organic-inorganic composite admixture, the steps are as follows:

[0024] Step 1, copolymerization reaction: free radical copolymerization reaction is carried out on monomer A, monomer B, monomer C, monomer D, an oxidant and a reducing agent, and the free radical copolymerization reaction is a conventional water system free radical copolymerization reaction;

[0025] Step 2: Electrostatic assembly reaction: Add polyoxometalate POM to the copolymer system in step 1, and perform magnetic stirring reaction at room temperature to complete the electrostatic assembly reaction.

[0026] The organic-inorganic composite admixture polymer has a weight average molecular weight of 60-100 kDa and a PDI of 2-3.

[0027] Preferably, in the free radical copolymerization reaction in step 1, the polymerization temperature is 35-55° C., the reaction time is 4-7 hours, and the polymerization concentration is 15-20%.

[0028] Preferably, the conditions for the room temperature magnetic stirring reaction in step 2 are: at room temperature (25° C.), the stirring rate is 600-1000 r / min, and the reaction time is 3-5 h.

[0029] Based on the above-mentioned organic-inorganic composite admixture as a calcined clay-limestone low carbon cement system (LC 3 ) in the application of admixtures. It can be used to enhance the effect of polycarboxylic acid admixtures on LC 3 The clay in the system has good resistance and can significantly improve the construction performance of concrete.

[0030] Preferably, the dosage of the organic-inorganic composite admixture is 0.1-0.2 wt%.

[0031] The principle of the present invention is as follows:

[0032] Cyclodextrin is a type of cyclic oligosaccharide composed of D-pyranose glucose units connected by α-(1-4) glycosidic bonds. According to the number of glucose units, cyclodextrin can be divided into α-, β-, γ-, δ-...θ-cyclodextrin, etc. Among them, β-cyclodextrin (abbreviated as β-CD) has a slightly conical hollow cylindrical three-dimensional ring structure, with a minimum inner diameter of the molecular cavity of about 0.61 nm and a maximum of about 0.78 nm; its height is about 0.78 nm, which has a significant steric hindrance effect. β-CD contains a large number of hydroxyl groups, and many cyclodextrin derivatives containing different functional groups can be obtained by modification. Relevant literature has pointed out that because the interlayer exchange ions of clay are cations, only the structural units with opposite charges will enter the crystal layers under electrostatic action to form an intercalated structure. Therefore, β-CD groups can be introduced into the molecular structure of polycarboxylic acid. Because they carry a negative charge, they can avoid entering the intercrystalline layers of clay due to electrostatic interaction, thereby preventing the chemical adsorption of polycarboxylic acid admixtures on clay. In addition, the polymer structure with large steric hindrance of the β-CD group also has an inhibitory effect on the interlayer intercalation adsorption of polycarboxylic acid molecules on clay.

[0033] Polyoxometalate (POM) is a molecular cluster formed by tetrahedral transition metal oxoate precursors in aqueous or organic solutions through co-point, co-edge or co-plane self-assembly. It is a special type of anionic metal oxide cluster with a variety of chemical compositions and rich topological structures. With the development of supramolecular chemistry, more and more polyoxometalates and their derivatives are widely used as inorganic building blocks to design and construct organic-inorganic hybrid materials with unique functional properties. The synergistic effect between inorganic nanomaterials and polymers gives polymer nanocomposites synergistically enhanced functions. One of the main characteristics is that the small size effect of inorganic nanoparticles leads to a sharp increase in the interface area between them and the polymer matrix. Introducing POM units into the molecular structure of polycarboxylic acid can further increase the steric hindrance of polycarboxylic acid molecules to ensure that they have high water-reducing and dispersing capabilities.

[0034] According to the structural characteristics and active effects of the commonly used anti-clay admixtures, β-CD and POM groups, the present invention attempts to solve the above problems from the perspective of synthesizing organic-inorganic composite polymer materials and thus improve the calcined clay-limestone low-carbon cement system (LC 3 ) Construction performance of concrete.

[0035] Therefore, the present invention provides an organic-inorganic composite admixture and a preparation method thereof and its application in calcined clay-limestone low carbon cement system (LC 3 ) by modifying the molecular structure of the admixture, introducing anti-clay functional monomers for modification, changing the structure of the polycarboxylic acid admixture molecules to improve their anti-clay properties, and at the same time ensuring the working performance of the admixture molecules, thereby realizing and solving the problem of large-scale promotion of the application of low-carbon cementitious systems in the concrete and construction industries.

[0036] The invention is applied to calcined clay-limestone low carbon cement (LC 3) system, carboxyl groups and sulfonic acid groups are distributed on the main chain and side chain (i.e., adsorption sites between cement-based materials), forming double adsorption sites, which can effectively improve the adsorption capacity, thereby fully realizing the high water reduction function; secondly, the significant spatial effect of β-CD in the organic-inorganic composite admixture and the nanostructure of POM form a spatial cross double network structure, resulting in a large spatial steric hindrance, forming a sufficiently thick adsorption layer, and further improving the dispersion ability of the admixture on cement particles; furthermore, the organic The inorganic composite admixture molecular structure does not contain the long side chain polyether monomers found in conventional polycarboxylic acid admixtures, which makes it difficult for it to form an intercalation structure with clay, preventing the admixture from being adsorbed by the clay; in addition, the AMPS unit can increase the absolute value of the Zeta potential on the clay surface, thereby further improving the dispersibility of the admixture in the system; finally, the nanostructure of POM has the small size effect of inorganic nanoparticles, which will cause the interface area between it and the polymer matrix to increase sharply, resulting in less adsorption of the admixture on the clay, further improving the efficient utilization of the admixture in concrete.

[0037] Beneficial effects:

[0038] (1) The present invention utilizes the structural characteristics of the organic-inorganic composite admixture, that is, through the significant spatial effect of the β-CD unit structure in the organic-inorganic composite admixture and the nanostructure of the POM unit to form a spatial cross double network structure, resulting in a large spatial steric hindrance and forming a sufficiently thick adsorption layer, which double hinders the intercalation adsorption of the admixture between clay layers and significantly improves the adaptability of the admixture.

[0039] (2) The present invention utilizes the carboxyl groups and sulfonic acid groups on the main chain and side chain in the molecular structure of the organic-inorganic composite admixture to form dual adsorption sites, thereby fully exerting the water-reducing effect.

[0040] (3) The present invention utilizes the POM unit in the organic-inorganic composite admixture. The small size effect of the inorganic nanoparticles will cause the interface area between the POM unit and the polymer matrix to increase sharply, which will result in less adsorption of the admixture on the clay, further improving the efficient utilization rate of the admixture in concrete. DETAILED DESCRIPTION

[0041] The present invention will be further described below in conjunction with specific embodiments.

[0042] In the examples of this specification, unless otherwise specified, the raw materials used are from common commercially available products.

[0043] The present invention provides a method for applying calcined clay-limestone low carbon cement (LC 3) system, which is formed by random copolymerization of monomer A (unsaturated carboxylic acid), monomer B (2-acrylamido-2-methylpropanesulfonic acid (AMPS)), monomer C (methacryloylpropyltrimethylammonium chloride (MAPTAC) or acrylamidopropyltrimethylammonium chloride (APTAC)) and monomer D (maleic anhydride grafted β-cyclodextrin (MAH-β-CD)) and then electrostatic interaction with POM (polyoxometalate).

[0044] The alkali metal ions in the examples of this specification are sodium and potassium.

[0045] The structural formula of the monomer A is shown in the following formula (I):

[0046] (I)

[0047] In formula (I), R 1 H or CH 3 , R 2 It is H or alkali metal ion.

[0048] Monomer A is specifically acrylic acid, methacrylic acid, sodium acrylate, and potassium acrylate.

[0049] The structural formula of the monomer B is shown in the following formula (II):

[0050] (II)

[0051] The structural formula of the monomer C is shown in the following formula (III):

[0052] (III)

[0053] In formula (III), R 3 H or CH 3 .

[0054] The structural formula of the monomer D is shown in the following formula (IV):

[0055] (IV)

[0056] In the formula (IV), M represents an alkali metal ion.

[0057] The weight average molecular weight Mw of the organic-inorganic composite admixture is 60-100 kDa, and the PDI is 2-3.

[0058] In addition, the embodiments described in the present invention can be applied to calcined clay-limestone low carbon cement (LC 3) system was determined by Shimadzu LC-20A high performance gel chromatography (GPC), where the chromatographic column was TSK G4000PWXL series, the column temperature was 25 °C, the eluent was 0.1 M sodium acetate aqueous solution, the flow rate was 0.5 ml / min, the injection volume was 15 μl of 1‰ sample aqueous solution, and the standard curve was prepared using dextran standards (Sigma-Aldrich).

[0059] The present application also provides a method for applying calcined clay-limestone low carbon cement (LC 3 The preparation method of the organic-inorganic composite admixture of the system is as follows:

[0060] (1) Copolymerization reaction:

[0061] Raw materials: monomer A, monomer B, monomer C and monomer D, monomer A is unsaturated carboxylic acid, monomer B is 2-acrylamido-2-methylpropanesulfonic acid (AMPS), monomer C is methacryloylpropyltrimethylammonium chloride (MAPTAC) or acrylamidopropyltrimethylammonium chloride (APTAC), and monomer D is maleic anhydride grafted β-cyclodextrin (MAH-β-CD). The mass ratio of monomer A, monomer B, monomer C and monomer D is 70: 15~25: 10: 0.5~1.5.

[0062] The oxidant is composed of a single oxidant, selected from any one of water-soluble azo oxidants, ammonium persulfate, sodium persulfate, and potassium persulfate, and the amount of the oxidant is 0.1-0.5 wt% of the total weight of the monomer. The reducing agent is one or two of sodium pyrosulfite, sodium sulfite, sodium bisulfite, sodium dithionite, sodium thiosulfate, and ferrous sulfate in any proportion, and the mass ratio of the reducing agent to the oxidant is 1:2.

[0063] Preparation steps: Mix monomer A, monomer B, monomer C and monomer D as well as an oxidant and a reductant, react at a temperature of 35-55° C. for 4-7 hours to carry out a free radical copolymerization reaction, wherein the free radical copolymerization reaction is a water system free radical copolymer reaction, and the polymerization concentration of the free radical copolymerization reaction is 15-20%.

[0064] (2) Electrostatic assembly reaction:

[0065] POM is added to the copolymer system obtained in the copolymerization reaction (1), with the mass ratio of POM to monomer C being 1:1.1-1.4, and a conventional magnetic stirring reaction is carried out at room temperature for 3-5 h at a stirring rate of 600-1000 r / min.

[0066] The following is an explanation through specific examples.

[0067] Example

[0068] Table 1 Raw material ratio table of the embodiment (feed ratio is the feed mass ratio of monomer A, monomer B, monomer C, and monomer D)

[0069]

[0070] Table 2 Process parameters of the embodiment (the amount of oxidant and reductant is the percentage of the total mass of the monomer)

[0071]

[0072] Comparative Example

[0073] The difference between Comparative Examples 1-6 and the embodiment is that the preparation process conditions of the admixtures are different, as shown in Table 3 and Table 4.

[0074] Table 3 Raw material ratio table of comparative example (feed ratio is the mass ratio of monomer A, monomer B, monomer C, and monomer D)

[0075]

[0076] Table 4 Process parameters of comparative examples (the amount of oxidant and reductant is the percentage of the total weight of the monomer)

[0077]

[0078] Application Examples

[0079] The application example of the present application provides a calcined clay-limestone low carbon cement system (LC 3 ).

[0080] The calcined clay-limestone low carbon cement system is composed of a mixture of the following materials:

[0081] (1) 30 parts by mass of calcined clay (CC)

[0082] (2) 15 parts by mass of limestone (L)

[0083] (3) 55 parts by mass of Portland cement (P)

[0084] The composition, particle size and calcination vector analysis tables of the calcined clay-limestone low-carbon cement system described in this application example are shown in Tables 5 to 7. The composition was measured using the Thermo Fisher ADVANT XP X-ray fluorescence spectrometer, and the particle size composition was measured using the Anton Paar PSA 1190LD laser particle size analyzer, wherein the calcined clay, limestone and Portland cement are all commercially available products.

[0085] Table 5 Calcined clay-limestone low carbon cement system (LC 3) Raw material composition table

[0086]

[0087] Table 6 Raw material particle size analysis table

[0088]

[0089] Table 7 Data table of raw material loss on ignition

[0090]

[0091] The organic-inorganic composite admixture prepared in Example 1-8 was added to the calcined clay-limestone low-carbon cement system to obtain Application Example 1-12.

[0092] The difference between Application Examples 1-12 is that the sources and dosages of the organic-inorganic composite admixtures are different, as shown in Table 8 for details.

[0093] Table 8 Sources and dosage of organic-inorganic composite admixtures in application examples 1-12

[0094]

[0095] Comparative Application Examples

[0096] The difference between the comparative application example and the application example is that the sources and dosages of the organic-inorganic composite admixtures are different, as shown in Table 9 for details.

[0097] Table 9 Sources and dosages of organic-inorganic composite admixtures for comparative application examples 1-6

[0098]

[0099] Performance testing:

[0100] Refer to the test method in GB / T 8077-2012 "Test method for homogeneity of concrete admixtures". Evaluate the effects of the admixtures in Application Examples 1-12 and Comparative Application Examples 1-6 on the freshly mixed calcined clay-limestone low carbon cement system (LC 3 ) The effect of the slurry fluidity and its loss over time was fixed at a water-cement ratio of 0.30. In addition, a comparison group was set up, and the admixture of the comparison group was the commercially available Cologne KL-1389 polyether anti-mud agent, in which the admixture dosage in comparison group 1 was 0.14 wt%, and the admixture dosage in comparison group 2 was 0.17 wt%. The experimental results are shown in Table 10.

[0101] Table 10 Performance test results

[0102]

[0103] Note: The percentages in the table refer to mass fractions.

[0104] From the experimental results in Table 10, it can be seen that the application of calcined clay-limestone low carbon cement system (LC 3 ), according to the performance comparison between application examples 1 to 8 and comparison group 1, under the same admixture dosage, the initial pure slurry fluidity and 1h slurry fluidity of the freshly mixed slurry of application examples 1 to 8 are higher than those of comparison group 1. Therefore, compared with the traditional comb-type cement dispersant, the organic-inorganic composite admixture of the present patent application has the characteristics of low dosage, high water reduction rate and excellent collapse retention performance even when applied to the calcined clay-limestone low-carbon cement system with high clay content.

[0105] In the organic-inorganic composite admixture of the present patent application, the carboxyl group and the sulfonic acid group in the molecular structure are used to form a double adsorption site, which can effectively improve the adsorption capacity, thereby fully realizing the high water reduction function; secondly, the significant spatial effect of the existing β-CD and the nanostructure of POM are used to form a spatial cross double network structure, resulting in a large spatial steric hindrance, forming a sufficiently thick adsorption layer, and further improving the dispersion ability of the admixture on cement particles; furthermore, the molecular structure of the admixture does not have the long side chain polyether monomer in the conventional polycarboxylic acid admixture, which makes it difficult to form an intercalation structure with clay, preventing the admixture from being adsorbed by clay, and can greatly reduce the influence of clay on the flow properties of the calcined clay-limestone low-carbon cement system. On the other hand, the small size effect of the POM unit with inorganic nanoparticles will cause a sharp increase in the interface area between it and the polymer matrix, which will result in less adsorption of the admixture on the clay, further improving the efficient utilization rate of the admixture in the calcined clay-limestone low-carbon cement system.

[0106] In addition, we also found that under the same dosage conditions, the dispersion effects of the admixtures in Application Examples 1 to 4 were also different. Finally, it was found that the performance of Application Example 3 was better than that of other application examples. This is because a larger or smaller molecular weight is not conducive to the admixture to exert its working performance. This is because the carboxylic acid and sulfonic acid groups in the admixture structure have a strong affinity for the cementitious material, so the admixture can be fixed on the surface of the cement particles, and the nanostructure of β-CD and POM will form a spatial cross-double network structure. When the admixture has a high molecular weight, the solution conformation of the molecular structure is too large, and the main chain structure will cause a cage effect on the adsorption sites, namely the carboxylic acid and sulfonic acid groups. When the molecular weight is too low, the adsorption site content is too low, which will cause the admixture to be unable to fix on the surface of the cement particles and unable to form an effective network structure, and thus unable to effectively hinder the adsorption of the admixture on the clay, making it difficult to improve LC 3 The initial fluidity of the system and its fluidity over time.

[0107] By analyzing application examples 5 and 6, it can be seen that when the number of repeating units of monomer B is small, the adsorption sites in the admixture, i.e., the sulfonic acid groups, will be too few and the dispersion performance will be too low, so the working performance of application example 5 is better than that of application example 6; from application examples 7 and 8, it can be seen that the working performance of application example 7 is better than that of application example 8, because the number of monomer D structure, i.e., the β-CD unit, should not be too high. If it is too high, the admixture itself will be entangled and agglomerated, and it will not be able to dissipate the calcined clay-limestone low carbon cement system (LC 3 ) system forms an effective dispersion.

[0108] At the same time, it is not difficult to find from application examples 9 to 12 that when the dosage of organic-inorganic composite admixture increases (0.1%→0.2%), LC 3 The initial fluidity of the fresh cement paste and its time-dependent fluidity of the system will experience a trend of first slowly increasing and then decreasing. Among them, Application Example 10 has the best effect, because when the dosage is too high, the double adsorption sites of the admixture will cause the bridge effect to easily cause secondary agglomeration, which will lead to the mutual entanglement between the chain segments in the admixture, thereby reducing the LC 3 The initial dispersion performance of the system eventually leads to a decrease in the overall working performance of the system.

[0109] Compared with application examples 1 to 8, the working performance of comparative application example 1 is significantly lower than that of the organic-inorganic composite admixture of the present invention applied to LC 3 The working performance of the system proves that the lack of carboxylic acid groups cannot form dual adsorption sites, and the sulfonic acid groups alone cannot effectively improve the adsorption capacity, which will be difficult to improve LC 3 The initial fluidity of the system; Comparative Application Example 2 has the worst working performance among all the application examples, proving that the lack of the corresponding β-CD structure will make it impossible to achieve a spatial cross-double network structure, and that the nanostructure of the POM unit alone cannot form an "isolation zone" between clay and cement-based materials, making it difficult to fully realize the high dispersion function.

[0110] Further analysis of the performance of comparative application examples 3 to 4 revealed that too few carboxylic acid groups in the admixture are not conducive to the dispersion performance of the admixture, but too many does not necessarily lead to the best working performance, indicating that there is a coordination relationship between the monomer A, monomer B, monomer C, monomer D and POM structure of the present application, and too much of a certain unit will affect the overall structural performance of the admixture. Combining the performance of comparative application examples 5 and 6, it was found that whether too much or too little monomer C and POM structure, the final application performance effect was not good, indicating that the number of monomer C and POM structure will affect the double network structure formed by it and the β-CD unit, and then affect the overall working performance of the admixture.

[0111] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An organic-inorganic composite admixture, characterized in that: The raw materials include the following components: monomer A, monomer B, monomer C, monomer D, polyoxometalate, oxidant and reducing agent, wherein monomer A is unsaturated carboxylic acid, monomer B is 2-acrylamido-2-methylpropanesulfonic acid, monomer C is methacryloylpropyltrimethylammonium chloride or acryloylpropyltrimethylammonium chloride, monomer D is maleic anhydride grafted beta-cyclodextrin, the mass ratio of monomer A, monomer B, monomer C and monomer D is 70:(15-25):10:(0.5-1.5), the mass ratio of the added amount of polyoxometalate to the monomer C is 1:1.1-1.4, the amount of the oxidant is 0.1-0.5 wt% of the total mass of the monomers, and the mass ratio of the reducing agent to the oxidant is 1:

2.

2. An organic-inorganic composite admixture according to claim 1, characterized in that: The polyoxometalate is phosphomolybdic acid H3[PMo 12 O 40 ] or silicomolybdic acid H4 [SiMo 12 O 40 ].

3. An organic-inorganic composite admixture according to claim 1, characterized in that: The oxidant is a water-soluble azo oxidant, ammonium persulfate, sodium persulfate or potassium persulfate.

4. The organic-inorganic composite admixture according to claim 1, characterized in that: The reducing agent is at least one of sodium pyrosulfite, sodium sulfite, sodium bisulfite, sodium dithionite, sodium thiosulfate and ferrous sulfate.

5. The organic-inorganic composite admixture according to claim 1, characterized in that: The structural formula of the unsaturated carboxylic acid is shown in the following formula (I): (I) Wherein, R1 is H or CH3, and R2 is H or an alkali metal ion.

6. A method for preparing an organic-inorganic composite admixture according to any one of claims 1 to 5, characterized in that: Here are the steps: Step 1, copolymerization reaction: free radical copolymerization reaction is carried out on monomer A, monomer B, monomer C, monomer D, an oxidant and a reducing agent, and the free radical copolymerization reaction is a conventional water system free radical copolymerization reaction; Step 2: Electrostatic assembly reaction: Add polyoxometalate to the copolymer system in step 1, and perform magnetic stirring reaction at room temperature to complete the electrostatic assembly reaction.

7. The method for preparing an organic-inorganic composite admixture according to claim 6, characterized in that: In the free radical copolymerization reaction in step 1, the polymerization temperature is 35-55° C., the reaction time is 4-7 h, and the polymerization concentration is 15-20%.

8. The method for preparing an organic-inorganic composite admixture according to claim 6, characterized in that: The conditions for the room temperature magnetic stirring reaction in step 2 are: at room temperature, the stirring rate is 600-1000 r / min, and the reaction time is 3-5 h.

9. Use of the organic-inorganic composite admixture according to claim 1 as an admixture for a calcined clay-limestone low-carbon cement system.

10. The use according to claim 9, characterized in that: The dosage of the organic-inorganic composite admixture is 0.1-0.2 wt%.

Citation Information

Patent Citations

  • Anti-crack low-carbon high-performance concrete and preparation method thereof

    CN115959870A

  • Low-carbon engineering cement-based composite material and preparation method thereof

    CN117105595A

  • Starch derivative copolymer and preparation method and application thereof

    CN102146150A

  • Preparation method for anti-mud-type polycarboxylic-acid water-reducing agent and application thereof

    CN104861127A

  • Dispersing agent, and preparation method and application thereof to dispersion of nano-alumina

    CN105457556A

Cited By

  • Low-carbon cement performance improver as well as preparation method and application thereof

    CN121990781A